Effectiveness of educational intervention in improving physical activity and nutritional performance among pregnant women: a pre-post quasi-experimental study using health belief model - Ali Khani Jeihooni; Fatemeh Razmjouie; Hanieh Jormand; Fariba Sedghi Jahromi; Pooyan Afzali Harsini; Amirhossein Kamyab; Farzaneh Ghaleh Golab (Frontiers in Global Women's Health)
BackgroundPhysical activity and proper nutrition during pregnancy are crucial for maternal and fetal health. However, many pregnant women fail to meet recommended guidelines. This study aimed to assess the effectiveness of an educational intervention based on the Health Belief Model (HBM) in improving these behaviors.MethodsA pre-post with control quasi-experimental study was conducted among 200 pregnant women (100 experimental and 100 control) in Shiraz, Iran. The intervention group attended eight weekly 50-minute educational sessions based on the HBM. Physical activity and nutritional performance were assessed using validated questionnaires at baseline and three months post-intervention. Data were analyzed using paired and independent t-tests, with effect sizes and 95% confidence intervals reported.ResultsThe intervention significantly improved physical activity (mean score: 29.25 ± 4.42 vs. 12.28 ± 4.36, p < 0.001) and nutritional performance across all food groups (p < 0.001) in the experimental group compared to the control group. Key constructs of the HBM, including perceived sensitivity, severity, benefits, self-efficacy, and cues to action, showed significant increases with notable effect sizes and 95% confidence intervals, while perceived barriers significantly decreased (p < 0.001).ConclusionsThe educational intervention based on the HBM effectively improved physical activity and nutritional performance among pregnant women. Integrating such programs into routine prenatal care is recommended, with emphasis on personalized counseling, regular follow-ups, and spousal involvement to sustain behavioral changes and promote maternal and fetal health.